Decoupling Functional and Morphological Convergence, the Study Case of Fossorial Mammalia - Sansalone, Gabriele; Castiglione, Silvia; Raia, Pasquale; Archer, Michael; Dickson, Blake; Hand, Suzanne; Piras, Paolo; Profico, Antonio; Wroe, Stephen (Frontiers in Earth Science, 2020)
Morphological similarity between biological structures in phylogenetically distant species is usually regarded as evidence of convergent evolution. Yet, phenotypic similarity is not always indicative of natural selection acting on a particular trait, and adaptation to similar conditions may fail to generate convergent lineages. Herein we tested whether convergent evolution occurred in the humerus of fossorial mammals, one of the most derived biological structures among mammals. Clades adapting to digging kinematics possess unusual, by mammalian standards, highly derived humeral shapes. The application of a new, computationally fast morphological test revealed a single significant instance of convergence pertaining to the Japanese fossorial moles (Mogera) and the North-American fossorial moles (Scalopini). Yet, the pattern only manifests when trade-off performance data (derived from finite element analysis) are added to shape data. This result indicates that fossorial mammals have found multiple solutions to the same adaptive challenge, independently moving around multiple adaptive peaks. This study suggests the importance of accounting for functional trade-off measures when studying morpho-functional convergence. We revealed that fossorial mammals, a classic example of convergent evolution, evolved multiple strategies to exploit the subterranean ecotope, characterized by different functional trade-offs rather than converging toward a single adaptive optimum.